Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1970
DOI: 10.3329/bjvm.v5i1.1322
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of trachea and lungs of buffaloes

Abstract: Pathological conditions of trachea and lungs of slaughtered buffaloes were investigated in the present study. A total of 80 slaughtered buffaloes were examined individually and trachea (80) and lungs (80) were collected for histopathology from the slaughterhouses of Barisal sadar, Barisal, Bangladesh, during the period from July 2006 to March 2007. Among them 9 trachea and 30 lungs were found to be apparently abnormal in naked eye. Grossly, tracheal and lungs lesions were 11.25% and 37.5% in buffaloes, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 3 publications
4
5
2
Order By: Relevance
“…This variation might be due to some calculating factor as authors calculated out of total examined goat but this investigation was conducted within only affected lungs of goats. Histopathology of bronchopneurnomia and hemorrhagic pneumonia described in this present investigation corresponded to the lesions of other investigators (Jones et al, 1997;Alam et al, 2001;Akbor et al, 2007). Pasteurella sp.…”
Section: Discussionsupporting
confidence: 91%
“…This variation might be due to some calculating factor as authors calculated out of total examined goat but this investigation was conducted within only affected lungs of goats. Histopathology of bronchopneurnomia and hemorrhagic pneumonia described in this present investigation corresponded to the lesions of other investigators (Jones et al, 1997;Alam et al, 2001;Akbor et al, 2007). Pasteurella sp.…”
Section: Discussionsupporting
confidence: 91%
“…The reason behind the higher rate of hemorrhagic lesion in buffalo is not clear at this moment and requires further investigation. The frequency of pulmonary congestion among the lung affections was 7.03% which is much less than the reports by Akbar et al (2007) that showed 16.25% of pulmonary congestions in buffalo lungs by gross examination. Pulmonary congestion occurs due to the obstruction of the pulmonary vessels and passive which is sometimes followed by pulmonary edema (Blood and Henderson, 1976).…”
Section: Discussioncontrasting
confidence: 60%
“…(Cullen and Maclachlan, 2001). Akbar et al (2007) and Rahman et al (2006) showed lower frequency of pulmonary nodules.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations